Erratum to "Accurate determination of film thickness by low-angle x-ray reflection". (1st September 2022) - Xu 徐, Ming 明; Yang 杨, Tao 涛; Yu 于, Wenxue 文学; Yang 杨, Ning 宁; Liu 刘, Cuixiu 翠秀; Mai 麦, Zhenhong 振洪; Lai 赖, Wuyan 武彦; Tao 陶, Kun 琨
Abstract : Equation (6) in Chin. Phys. 09 0833 (2000) is corrected. All subsequent derivations were given based on the correct Eq. (6), so the conclusions in the paper are not affected by the errata.